Plant community dynamics of lomas fog oasis of Central Peru after the extreme precipitation caused by the 1997-98 El Nino event - Tovar, C (2018)
This work was supported by Concejo Nacional de Ciencias y Tecnologia (CONCYTEC)-Peru; Universidad Nacional Agraria La Molina. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.